Anatomical Study of Venous Valves and Valve-like Structures in the Superficial Temporal Veins: Implications for Reconstructive Surgery - Wang, Yunzhang; Cao, Zilong; Yue, Qiang; Rui, Shu; Zhang, Tiran; Liu, Liqiang (Journal of Reconstructive Microsurgery)
Background: Detailed knowledge of venous valves and valve-like structures is essential in reconstructive surgery, as these structures may contribute to postoperative venous congestion following flap transfer. However, their presence in the superficial temporal veins (STVs), which are frequently utilized in craniofacial reconstruction, remains unclear. The authors performed morphological and morphometrical examinations of venous valves and valve-like structures in the STVs through cadaver dissection. Methods: This study involved the longitudinal dissection of 24 STVs from 12 cadavers. The veins were then examined under a stereomicroscope to determine the presence of venous valves or valve-like structures, and their quantity and location were recorded. Results: The STVs contain both venous valves and valve-like structures known as venous cristae. All observed venous valves were bicuspid, while venous cristae were characterized by ridge-like protrusions of venous wall into the lumen. A total of 5 venous valves and 69 cristae were identified across 24 STVs. Venous valves were exclusively located in the main trunks of the STVs, whereas venous cristae were classified into five types based on their locations, with venous bifurcations being the most common sites. Most main trunks（22/24）contained either one venous valve or one crista, and the average distances from these structures to the superior margin of the zygomatic arch were 8.42 ± 0.80 mm and 9.03 ± 0.86 mm, respectively. Conclusion: A comprehensive understanding of the characteristics, quantity, and distribution of venous valves and cristae in the STVs could provide valuable insights for surgeons in preventing postoperative venous congestion.